A Weak Convergence Theorem for a Finite Family of Asymptotically Nonexpansive Mappings (Communications in Mathematical Research, 2021)
The purpose of this paper is to prove a new weak convergence theorem fora finite family of asymptotically nonexpansive mappings in uniformly convex Banachspace.